Pengaruh Material Reflektor Terhadap Kinerja Kompor Energi Surya - Napitupulu, Richard A M; Manurung, Charles S.P; Naibaho, Waldemar; Sihombing, Suriady (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2022)
The use of solar energy in Indonesia is the right choice as an alternative energy for energy needs in industry or to meet daily energy needs in households. To utilize solar energy for cooking purposes, a solar cooker can be used. Factors that affect the performance of this solar cooker in addition to the length of time it shines and the intensity of thermal radiation from the sun are the reflexivity of the collector material, the surface area of ​​the collector, the geometric shape and location of the focal point of the collector, the normal direction of the collector surface to the incoming sunlight, and the amount of heat loss to the surroundings. The materials used as reflectors in the research on this solar cooker are zinc (aluminum and galvanized) AL-Zn and black paint back ground mirror glass. This material is re-glued on top of a ready-made parabolic dish from the market. Then look for the focal point that corresponds to the diameter of the parabola. From the results of the study, it can be concluded that the back ground mirror glass material with black paint is better to use than the AL-Zn zinc plate if it is used as a raw material for the surface material (reflector) of solar cooker. Likewise, the efficiency of the solar oven in terms of the amount of heat that is converted into energy for heating the pot is better for a solar oven than a reflector with black paint back ground mirror glass material. And the efficiency of the solar cooker from the black paint back ground mirror on the first day is 16.4% to 25.7% on the second day, while the efficiency of the solar cooker from the AL-Zn zinc plate on the first day is 16.4% to second day 22.8%. The emissivity of the solar stove with AL-Zn zinc plate reflector on the first day was 0.02906 and on the second day 0.02892, while the emissivity of the solar cooker with black paint back ground mirror reflector on the first day was 0.01812 and the second day was 0 0.02544.